Curriculum Adaptation and Educational Technology Implementation in Border Areas: Infrastructure Challenges and Teachers’ Adaptive Strategies at SMP Negeri 2 Kefamenanu, East Nusa Tenggara - Feliksitas Angel Masing; Lamijan Hadi Susarno; Bachtiar Syaiful Bachri (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to explore curriculum adaptation in border regions facing challenges in implementing educational technology amid infrastructure limitations, with a case study at SMP Negeri 2 Kefamenanu, East Nusa Tenggara. A qualitative case study approach was employed. Data were collected through in-depth semi-structured interviews with an Indonesian Language teacher who participated in the Guru Penggerak (Teacher Mover) program. Five major themes emerged: (1) limited infrastructure conditions, (2) adaptive implementation of the Merdeka Curriculum, (3) technology integration strategies under constraints, (4) digital competency gaps between teacher generations, and (5) local culture-based contextualization of learning materials. Findings reveal that despite significant infrastructure limitations, meaningful learning continues through adaptive strategies developed by teachers. This study contributes to the literature on curriculum adaptation and educational technology by emphasizing contextual approaches and highlighting the need for more affirmative educational policies for border regions.